Pengaruh Harga, Kepercayaan dan E-Wom Terhadap Minat Beli Ulang Permasi Textile Banda Aceh - Maulidi, Syahrul; Marlizar; Al Rizky, Mahfud (JIMEBIS: Scientific Journal of Students Islamic Economics and Business, 2023)
This study aims to determine the effect of Price, Trust and Electrical Word Of Mouth simultaneously on repurchase interest at the Banda Aceh Textile Permasi Store. The method used is a causal associative method that aims to determine the influence or relationship between two or more variables in a study. Determination of this study sample using accidental sampling technique. The sample used in this study was 96 consumers in textile permasi Banda Aceh who had purchased products more than once and were willing to become respondents. The analysis method applied is multiple linear regression analysis. The results showed that the price partially affected the repurchase interest in Permasi Textile Banda Aceh. Trust partially affects repurchase interest in Permasi Textile Banda Aceh. Electric Word Of Mouth partially affects repurchase interest in Permasi Textile Banda Aceh. Price, Trust and E-WOM simultaneously affect repurchase interest in Banda Aceh textile permasi. The increase in repurchase interest is determined by Price, Trust and E-Wom the more affordable the price, the stronger the trust and the high E-Wom owned by business actors, the greater the opportunity for companies to increase consumer repurchase interest.